DC Bus Instability Driving by Photovoltaic Source with Constant Power Load - Mohd Nasir, Mohamad Na'im; Alias , Khamis (Trans Tech Publications, 2013)
This study presented the DC bus instability in distributed power system driving by Photovoltaic (PV) source with constant power load (CPL). The aim of this study is to investigate the effect of PV source towards the performances of DC bus voltage stability using constant power load The system first was tested using linear DC supply as voltage source and CPL was modeled and connected to the voltage source through LC filter network. A passive damping circuit was chosen to stabilize the DC bus instability. The system was repeated using PV source. PV array was modeled based on the parameters obtained from a commercial PV data sheet. A circuitry simulation was performed under the similar design excluding the DC source in order to investigate DC bus instability. Results showed that the stability of DC bus become unstable when using linear DC voltage supply and slightly affected when using PV source. The instability phenomenon due to the negative incremental impedance of a constant power load can be overcome by using damping technique. For linear DC voltage source, DC bus voltage system tends to oscillate. However, with PV source which is actually a current source input seems not much affecting the DC bus voltage stability.using PV source. PV array was modeled based on the parameters obtained from a commercial PV data sheet. A circuitry simulation was performed under the similar design excluding the DC source in order to investigate DC bus instability. Results showed that the stability of DC bus become unstable when using linear DC voltage supply and slightly affected when using PV source. The instability phenomenon due to the negative incremental impedance of a constant power load can be overcome by using damping technique. For linear DC voltage source, DC bus voltage system tends to oscillate. However, with PV source which is actually a current source input seems not much affecting the DC bus voltage stability.